2020
DOI: 10.3847/1538-4357/abb0ea
|View full text |Cite
|
Sign up to set email alerts
|

Rotation Curves in z ∼ 1–2 Star-forming Disks: Evidence for Cored Dark Matter Distributions

Abstract: We report high quality, Hα or CO rotation curves (RCs) to several Re for 41 large, massive, star-forming disk galaxies (SFGs), across the peak of cosmic galaxy evolution (z~0.67-2.45), taken with the ESO-VLT, the LBT and IRAM-NOEMA. Most RC41 SFGs have reflection symmetric RCs plausibly described by equilibrium dynamics. We fit the major axis position-velocity cuts with beam-convolved, forward modeling with a bulge, a turbulent rotating disk, and a dark matter (DM) halo. We include priors for stellar and molec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
151
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(180 citation statements)
references
References 211 publications
25
151
4
Order By: Relevance
“…Therefore, V DM (r) is determined by a single parameter M 200 in this simple dark matter halo model. The total circular velocity of the baryonic disk and the dark matter halo model (Burkert et al 2010(Burkert et al , 2016Lang et al 2017;Genzel et al 2020) is calculated by…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, V DM (r) is determined by a single parameter M 200 in this simple dark matter halo model. The total circular velocity of the baryonic disk and the dark matter halo model (Burkert et al 2010(Burkert et al , 2016Lang et al 2017;Genzel et al 2020) is calculated by…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we should take into account the effect of the pressure support in RCs. Assuming the velocity dispersion σ 0 is constant in the exponential disk model in hydrostatic equilibrium, the observed RC (Burkert et al 2010(Burkert et al , 2016Lang et al 2017;Genzel et al 2020;Kretschmer et al 2021) is described by 11). The contributions to the total rotation curve from the dark matter halo (Equation 7) and the baryonic disk (Noordermeer 2008) are indicated by the dashed line and the blue solid line, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…, where FWHM is in km s −1 and r e in kpc, and we adopt sin 2 (i) = 2/3 (Tacconi et al 2008). For dark matter fraction, we adopt f DM = 0.12 based on the latest dynamical studies of z ∼ 2 star-forming galaxies with analyses of high-quality rotational curves (Genzel et al 2020). In the bottom-left panel of Figure 3 we plot three lines representing three gas mass fractions respectively, in which we also plot our measurements along with those from the z = 2 − 5 unlensed sources in the literature.…”
Section: Molecular Gas Fraction and Star Formation Efficiencymentioning
confidence: 99%
“…Disk-halo decompositions have proven to be possible at z 2 in the pioneering work of Genzel et al (2017) using very deep (> 30 hr) near-IR integral field spectroscopy (IFS) on a small sample of six massive starforming galaxies (SFGs). Exploring lower mass SFGs, this exercise requires a stacking approach (as in Lang et al 2017;Tiley et al 2019) or deep IFS observations (as in Genzel et al 2020). These studies of massive SFGs with M > 10 11 M showed that RCs are declining at large radii, indicative of a low DM fraction within R e ; see also Wuyts et al (2016); Übler et al (2017); Abril-Melgarejo et al (2021) for dynamical estimates of DM fractions.…”
Section: Introductionmentioning
confidence: 99%